Isoform selectivity of harmine-conjugated 1, 2, 3-triazoles against human monoamine oxidase. (22nd May 2018) - Haider, Saqlain; Alhusban, Manal; Chaurasiya, Narayan D; Tekwani, Babu L; Chittiboyina, Amar G; Khan, Ikhlas A
Aim: There is little information available on the monoamine oxidase isoform selectivity of N -alkyl harmine analogs, which exhibit a myriad of activities including MAO-A, DYRK1A and cytotoxicity to several select cancer cell lines.Results: Compounds3e and4c exhibited an IC50 of 0.83 ± 0.03 and 0.43 ± 0.002 μM against MAO-A and an IC50 of 0.26 ± 0.04 and 0.36 ± 0.001 μM against MAO-B, respectively. Molecular docking studies revealed π–π interactions between the synthesized molecules and aromatic amino acid residues.Conclusion & future perspective: The current study delineates the structural requirements for MAO-A selectivity and such information may be helpful in designing selective analogs for kinase, DYRK1A and harmine-based cytotoxics without apparent MAO enzyme inhibition.